STRATEGI PEMASARAN TERHADAP K-STREET BYUNDONG DALAM MENGHADAPI PASAR DI ERA PANDEMI COVID-19 DI KOTA PURBALINGGA - Yeristha Asrillia, Auriel; Rohmah, Fitri Nur; Mawarni, Mita; Prasetyani, Oki Dwi (Perwira Journal of Economics & Business, 2022)
MSMEs are trading businesses managed by individuals who have economic businesses with criteria that have been applied by law. Even in terms of management, it still has a close relationship with the community's economy. However, around the beginning of March 2020, Indonesia was hit by an outbreak of a disease called Covid-19 (Corona Virus). Corona virus is a contagious disease. The global Covid-19 pandemic certainly has an impact on various sectors, especially in the economic sector. This study aims to examine the strategy of K-Street ByungDong in dealing with the market in the era of the Covid-19 pandemic and find out the efforts made by K-Street ByungDong in overcoming marketing constraints during the Covid-19 pandemic. The research method used in this study is a descriptive qualitative method. In this study, the object of research is the strategy of K-Street ByungDong in dealing with the market in the era of the Covid-19 pandemic. Data analysis methods used are interviews and documentation. Based on the results of the study, it shows that digital marketing is effectively carried out as a marketing strategy in dealing with the market in the era of the covid-19 pandemic